ESRA19-0591 A prospective observational study of clinical outcomes associated with proficiency-based progression training in epidural insertion for patients in labour. (30th August 2019) - Ahmed, H; McAulliffe, N; Srinivasan, K; O'Connor, R; Shorten, G
Abstract : Background and aims: Efforts to move from time-based to outcome-based training have led to development of novel training methodologies including Proficiency-Based Progression (PBP). Recently, our group has demonstrated that PBP training based on pre-defined metrics improves not just physician performance, but meaningful patient outcome (53% decrease in failure incidence of epidurals placed by anaesthetic trainees). The principal objective of this study is to examine for association (i) quality of performance (in a simulated setting) of epidural insertion by novices following PBP training and (ii) subsequent success in achieving epidural analgesia for labouring parturients. Methods: With institutional ethical approval, all trainees in anaesthesiology scheduled to train in obstetric anaesthesia during 2019–2020 will be invited to participate. Following baseline testing, trainees will undertake PBP training with one-to-one supervision of a consultant anaesthetist trained in PBP. Detailed descriptions of pre-defined metrics will be provided. Each will then practice each metric in a simulated setting with metrics-based feedback in real time. Trainees will proceed to the clinical phase when they have attained the pre-defined proficiency benchmark. All subsequent attempts of labour epidural catheter placement will be documented. Overall incidence of success and other performance parameters will be calculated and compared with historical reports. Results: This study is still recruiting. We successfully trained three novices who performed 32 labour epidural catheter placements. The proportion of epidural failure was 21.9% (7/32), the proportion of supervisor takeover was 16% (6/32), difficulty to insert epidural due to patient factors was 13% (5/32), patient satisfaction with the epidural performance is 8.6 ± 1.9. Conclusions: This study is recruiting.